Effect of hemp seed oil on accelerating wound healing: Evaluation of wound size reduction, epithelialization, granulation tissue formation, and vascularization in murine models - Rahman, Safrizal; A. Rivai, Mohammad; Dasrul, Dasrul; Ayu, Onarisa (Narra Sains Indonesia, 2025)
Essential oils have gained interest in wound management, with prior studies exploring combinations of hemp seed oil (Cannabis sativa) and other oils. However, single-oil strategies may offer simpler formulation, reducing the risk of interactions while preserving therapeutic benefits. The aim of this study was to explore the effect of hemp seed oil on accelerating wound healing, focusing on wound size reduction, epithelialization, granulation tissue formation, and vascularization in murine models. An in vivo with a post-test-only control group was conducted using 36 male Mus musculus mice (3−4 months, 150–250 grams) which were divided into three groups: negative control (NC), positive control (PC, treated with chloramphenicol ointment twice daily), and treatment group (TG, treated with hemp seed oil 400,000 mg/mL twice daily). Mice were euthanized on day 3, 7, 14, and 21 for wound healing assessment, including macroscopic evaluation (visual observation, wound size, and wound healing rate) and microscopic evaluation (epithelialization, granulation tissue formation, and vascularization). The present study found that the TG group demonstrated smaller wound sizes on day 14 (p<0.001) and day 21 (p<0.001). This group also enhanced wound healing rates observed on day 14 (p<0.001) and day 21 (p=0.001) compared to PC and NC groups. Epithelialization was significantly higher in the TG group compared to PC and NC groups on day 14 (p=0.007), while granulation tissue formation showed significant improvement on day 3 (p=0.045), day 14 (p=0.028), and day 21 (p=0.003). Additionally, TG group showed significantly greater new blood vessel formation on day 21 (p=0.001) compared to the PC and NC groups. In conclusion, hemp seed oil demonstrated significant potential in accelerating wound healing processes suggesting a superior effect compared to chloramphenicol ointment. Therefore, hemp seed oil may serve as a promising natural and cost-effective adjunct for wound management.